Growing Up with Digital Technologies: How the Precautionary Principle Might Contribute to Addressing Potential Serious Harm to Children's Rights. Issue 2 (3rd April 2021) - Lievens, Eva
ABSTRACT: Digital technologies affect the lives of children and the rights that are specifically attributed to them by the United Nations Convention on the Rights of the Child (UNCRC), article 24 of the EU Charter of Fundamental Rights and many national constitutions. There is no doubt that the digital environment has enormous potential for the empowerment of children and their exercise of the UNCRC rights. Yet, children (and their parents) are expected to make difficult decisions about whether or not or how to use platforms, devices and services that function in complex and opaque manners and whose impact on the rights of the child are difficult to grasp. This is especially the case for data- and advertising-driven practices that intentionally deceive or manipulate children or that are based on pervasive tracking and inferences about children's behaviour, attention and emotions. Based on a legal study of the UNCRC, legislation and policy documents at UN, Council of Europe and European Union level, and scholarship, this article studies the extent to which duties and responsibilities rest on policymakers, platforms and service providers and regulators to uphold the best interests of the child as a primary consideration (Article 3 (1) UNCRC) and what this means for the digital spaces in which children grow up. In particular, the article explores how the application of the precautionary principle might better serve the best interests of the child and how this might require legal restrictions on certain practices, enhanced responsibilities for public and private actors, and stronger enforcement by regulators.